The role of social identity in shaping economic choices: Evidence from women’s self-help groups in India - Alvi, Muzna; Raghunathan, Kalyani; Sehgal, Mrignyani (International Food Policy Research Institute, 2019)
Group-based interventions are fast gaining traction in developing countries, often bolstering existing government service delivery systems. Such groups provide development programs with a means of extending their reach to households and individuals that might otherwise not seek public goods and services. However, the very reliance on the notion of “community” in these programs can constrain participation to those with a shared identity. In India, shared caste identity remains a central, and often controversial, element in many community-based programs. We explore the salience of caste identity with a field experiment conducted among women’s self-help groups in an eastern state of India. The experiment focused on the provision of information on nutrition, diet, and kitchen gardens. Specifically, we test the interplay between (a) the provision of information to self-help groups and (b) the caste identity of the information provider relative to the group’s caste identity, to assess what matters more –the message or the messenger. We randomize two treatments – an information treatment and ahomophily treatment – and measure the effect of these treatments on two outcomes: group members’willingness to contribute to a group-owned club good (a collectively managed kitchen garden), andindividual members’ retention of the information they received. We find that (1) information is veryimportant, (2) homophily, or shared caste identity with the information provider, is not that important,but (3) higher-caste information providers elicit greater willingness to contribute. These findings haveseveral implications for the design of public programs that rely on community-based organizations andagents as implementing partners and may thus be susceptible to identity issues, such as the exclusionof lower castes from certain occupations, public spaces or public goods.